Ethics and the beast : an speciesist argument for animal liberationism - Zamir, Tzachi, 1967- (Princeton University Press, 2007)
Many people think that animal liberation would require a fundamental transformation of basic beliefs. We would have to give up "speciesism" and start viewing animals as our equals, with rights and moral status. And we would have to apply these beliefs in an all-or-nothing way. But in Ethics and the Beast, Tzachi Zamir makes the radical argument that animal liberation doesn't require such radical arguments--and that liberation could be accomplished in a flexible and pragmatic way. By making a case for liberation that is based primarily on common moral intuitions and beliefs, and that therefore